Manajemen Tahfiz Al-Qur’an di RA Al Firdaus Kisaran Timur Asahan - Nurhani Nurhani; Fuji Rahmadi P (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
Early childhood education institutions in the modern era offer various superior programs, one of which is the Al-Qur’an tahfiz program. Implementing the Tahfiz Al-Qur’an program requires good management with the stages of planning, organizing, implementing and monitoring. For young children who have a tendency to play, they need to manage memorization activities in an interesting and fun way. The aim of this research is to determine the management of the Al-Qur’an tahfiz program at RA Al Firdaus Kisaran Timur Asahan. The method used in this research is qualitative with data collection techniques using participant observation and in-depth interviews. All existing data is analyzed using the stages of data condensation, data display and verification. The findings in this research are that in the tahfiz Al-Qur'an program at RA Al Firdaus, the planning carried out was a clear formulation of the vision, mission, goals, targets and learning tools. In the organizing process, efforts were made to group children's ages by memorization level and target. In implementation, school principals and teachers have a strong commitment and various methods that are relevant and interesting and there is no coercion in teaching children to memorize the Al-Qur’an. Furthermore, in supervision, the institution carries out a program of observation, supervision, daily and end-of-semester assessments. Supervision is carried out by the principal and teachers at RA Al Firdaus on an ongoing basis and in collaboration with parents.